2017
DOI: 10.1186/s12885-017-3356-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 receptor affects the survival of primary prostate cancer patients depending on TMPRSS2-ERG status

Abstract: BackgroundProstate cancer (PCa) is characterized by clinical and biological heterogeneity and has differential outcomes and mortality rates. Therefore, it is necessary to identify molecular alterations to define new therapeutic strategies based on the risk of progression. In this study, the prognostic relevance of the insulin-like growth factor (IGF) system was examined in molecular subtypes defined by TMPRSS2-ERG (T2E) gene fusion within a series of patients with primary localized PCa.MethodsA cohort of 270 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
2
9
1
Order By: Relevance
“…The only other cohort study that has investigated cancer outcomes examined mRNA expression of IGF1R and IR in among 270 patients and used biochemical recurrence rather than lethal prostate cancer as the end point (14). Although they found a positive correlation between IGF1R, IR and ERG, they found that IR and IGF1R expression were downregulated in tumor versus benign tissue, which contrasts with our study findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The only other cohort study that has investigated cancer outcomes examined mRNA expression of IGF1R and IR in among 270 patients and used biochemical recurrence rather than lethal prostate cancer as the end point (14). Although they found a positive correlation between IGF1R, IR and ERG, they found that IR and IGF1R expression were downregulated in tumor versus benign tissue, which contrasts with our study findings.…”
Section: Discussioncontrasting
confidence: 99%
“…There is limited evidence to date on IGF1R and IR expression in tumor tissue and prostate cancer progression in patient cohorts, and none have used lethal disease as an end point (14). We hypothesized that higher tumor expression of IGF1R and IR would be associated with an increased risk of lethal prostate cancer, with a stronger effect in men whose tumors were positive for ERG.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up, IGF-IR expression showed a borderline association with increased risk of lethal disease [136]. In contrast a study of samples from 270 men with more than 5 years follow-up reported that in men who were negative for the TMPRSS2-ERG gene fusion, high IGF-IR was associated with prolonged biochemical progression free survival [137].…”
Section: Evidence From Clinical Studiesmentioning
confidence: 91%
“…For instance, a recent comprehensive systematic review and meta-analysis suggested a link between milk ingestion and PCa through the modulation of IGFs [ 20 ]. Another clinical study linked the prognosis of PCa to the overexpression of IGFR-1 receptor in transmembrane serine protease 2-erythroblast transformation-specific-related gene (TMPRSS2-ERG) (T2E) gene-negative subgroup of patients [ 21 ].…”
Section: Growth Factors Involved In Prostate Cancermentioning
confidence: 99%